Elderly Characteristics with Frailty Syndrome by Frailty Index Questionnaire – 40 (FI - 40) at Bandung Nursing Home - Ivany R Rahmadani; Lazuardhi Dwipa; Yuni S Pratiwi (Journal of Medicine and Health, 2018)
Frailty syndrome is a state of decreased body function, thereby increasing susceptibility to poor clinical outcomes. The risks of developing frailty syndrome increase in the elderly at Nursing Home. This study is expected to provide characteristic data of frailty syndrome as the basis for the prevention and management for the elderly. This study is conducted by using a descriptive quantitative design. The data is taken by using FI-40 questionnaire consisting of 40 questions in the elderly at Bandung done by using total sampling. There are 42(58.3%) of pre-frail and 7(9.7%) of frail elderly out of 72 data. Pre-frail prevails mostly in women (29 subjects; 69.1%) and at age of 60-69 years in 18 subjects (42.8%). Frail elderly is found mostly in women (3 subjects; 42.8%) and aged 70-79 years (3 subjects ; (42.8). The most common cause of frailty is eye and foot problems in 7(100%). The most common cause of pre-frail is the assumption of health level in 35(83.3%). This study concludes that frailty syndrome is common among the elderly and special attention must be paid to eye and foot problems.Keywords: elderly, frailty syndrome, FI-40 questionnaire, nursing home